Inflammatory characterization of different non-allergic rhinitis in patients attending tertiary care hospital - Sharma, Ashish; Pyadala, Nagababu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Non-allergic rhinitis is a chronic inflammation of nasal cavity, which can be classified based on the level of eosinophil. Thus, the present study aimed to characterize the various types of non-allergic rhinitis. Methods: This study conducted during the period of 1 year from April 2019 to February 2020 in the ENT department of MNR Medical College and Hospital, Sangareddy. A total of 60 participants were enrolled in this study. Results: In case of non-allergic rhinitis, the nasal IL-17 level was 27.31±5.1, IL-4 level was 44.24±21.31, as well as serum IL-4 and IL-17 level was 50.1 and 31.06 respectively. The control group IL-4 and IL-17 level were respectively less (p<0.05). But the IL-10 level (3.7) and proportion of tregs in peripheral blood (5.2) were lower than the control group (p<0.05). There was no significant difference found between the non-allergic rhinitis group and allergic rhinitis group or the non-allergic rhinitis without eosinophilia group and the control group (p>0.05). Conclusions: Hence, the non-allergic rhinitis was classified on the basis of eosinophil level, allergic rhinitis and NARES had similar kind of inflammatory response, but two different types of non-allergic rhinitis had different inflammatory characteristics. Therefore, it is recommended to classify the rhinitis on the basis of eosinophil level.